Analysis of properties of optical carriers after long-term storage - Petrov, V.V.; Kryuchyn, A.A.; Gorbov, I.V.; Kossko, I.O.; Kostyukevych, S.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Performed in this paper is the analysis of possibilities to create optical information carriers for long-term information storage. Adduced are the results of experimental investigations of properties inherent to optical carriers of the WORM type after 25-year storage. It has been shown that their micro-relief structure formed by using focused laser radiation on thin films of chalcogenide vitreous semiconductors had not been practically changed after storing them for the above mentioned period in non-heated areas.